Methods and Frameworks in Sustainable Product Design and Development: A Narrative Literature Review - Widya Rahmadani Utami; Rosnani Ginting; Ukurta Tarigan (TALENTA Publisher, 2026)
This literature review examines the application of methods such as Life Cycle Assessment (LCA), Design for Environment (DfE), Cradle to Cradle (C2C), Biomimicry, Circular Economy, and Sustainable Material Selection (SMS) in Sustainable Product Design & Development (SPDD). This study aims to synthesize existing research on the benefits, challenges, and integration of methods for environmentally sustainable product design through a narrative literature review of academic sources from 2008 to 2025, including textbooks and journals such as the Journal of Cleaner Production. The findings highlight that these methods collectively reduce environmental impacts by up to 70%, enhance resource efficiency, and foster innovation. However, challenges such as high implementation costs, data scarcity, and scalability issues persist. This review argues that an integrated framework combining LCA, DfE, and Circular Economy effectively mitigates these barriers by streamlining data requirements and optimizing long term cost efficiency through proactive design. Consequently, this integrated approach offers optimal outcomes for sustainable product development while supporting global regulations. Future research should prioritize empirical studies and interdisciplinary collaboration to further bridge the gap between theoretical frameworks and practical application.